2023
DOI: 10.1002/adma.202302335
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Small High‐Entropy Alloy Nanoparticles: Efficient Nanozyme for Enhancing Tumor Photothermal Therapy

Abstract: High‐entropy alloys nanoparticles (HEANPs) are receiving extensive attention due to their broad compositional tunability and unlimited potential in bioapplication. However, developing new methods to prepare ultra‐small high‐entropy alloy nanoparticles (US‐HEANPs) faces severe challenges owing to their intrinsic thermodynamic instability. Furthermore, there are few reports on studying the effect of HEANPs in tumor therapy. Herein, the fabricated PtPdRuRhIr US‐HEANPs act as bifunctional nanoplatforms for the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…PTT is considered a noninvasive therapeutic modality that utilizes photothermal agents to convert light energy into hyperthermia, thereby inducing apoptosis and necrosis in tumor cells. , Importantly, the localized elevation of temperature resulting from PTT significantly enhances the catalytic activity of nanozymes, thereby achieving augmented catalytic therapy. , For example, Yang et al developed Ti 3 C 2 T x -Pt-PEG nanocomposites, in which Pt was used as a POD-like nanozyme and Ti 3 C 2 T x served as a photothermal agent for photothermal enhanced catalytic therapy (Figure A) . The photothermal-conversion efficiency of Ti 3 C 2 T x -Pt-PEG nanocomposites was calculated to be 31.78%, demonstrating the superior photothermal performance of Ti 3 C 2 T x -Pt-PEG.…”
Section: Application Of Nanozymes In Enhancing Anticancer Effectsmentioning
confidence: 99%
“…PTT is considered a noninvasive therapeutic modality that utilizes photothermal agents to convert light energy into hyperthermia, thereby inducing apoptosis and necrosis in tumor cells. , Importantly, the localized elevation of temperature resulting from PTT significantly enhances the catalytic activity of nanozymes, thereby achieving augmented catalytic therapy. , For example, Yang et al developed Ti 3 C 2 T x -Pt-PEG nanocomposites, in which Pt was used as a POD-like nanozyme and Ti 3 C 2 T x served as a photothermal agent for photothermal enhanced catalytic therapy (Figure A) . The photothermal-conversion efficiency of Ti 3 C 2 T x -Pt-PEG nanocomposites was calculated to be 31.78%, demonstrating the superior photothermal performance of Ti 3 C 2 T x -Pt-PEG.…”
Section: Application Of Nanozymes In Enhancing Anticancer Effectsmentioning
confidence: 99%
“…As reported, the catalytic efficiency can be clearly tailored by modulating the compositions, sizes, and morphologies of noble metal-based nanozymes, so it is expected to achieve efficient enzyme-like activity by finely regulating the structures and morphologies of nanozymes. Notably, it has been shown that palladium nanocrystals display facet-dependent CAT-like and OXD-like properties. , Thus, a Pd-based nanozyme with concurrently exposed Pd(111) and Pd(100) facets would be extremely efficient for synergetic CAT- and OXD-like dual therapy to produce highly toxic 1 O 2 via cascade catalysis. Moreover, it is found that compared with other precious metals, Pd has the highest decomposition energy barrier to activate H 2 O 2 for producing •OH, which is conducive to the formation of more 1 O 2 . However, the limited electron transport and intrinsic electronic structure of monometallic materials restrict their catalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is found that compared with other precious metals, Pd has the highest decomposition energy barrier to activate H 2 O 2 for producing •OH, which is conducive to the formation of more 1 O 2 . 14 However, the limited electron transport and intrinsic electronic structure of monometallic materials restrict their catalytic activity. 15 Consequently, the growing evidence suggests that multimetal alloy nanozymes should be studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the past five years, HEA research has predominantly focused on synthesizing HEA nanoparticles and exploring their applications in energy-related fields, including catalysis, 6–15 electrochemical energy storage, 11,16–20 and light harvesting and conversion. 21–26 The emergence of HEA nanomaterials and their promising properties have attracted extensive attention and resulted in some review articles primarily focused on catalysis. 8,9,11–14 Although the synthesis of HEA nanomaterials is crucial for exploring their unique properties, a focused and insightful overview of synthetic strategies is still rare in the literature.…”
Section: Introductionmentioning
confidence: 99%